Determining heavy metal levels in surface water samples from selected creeks in Rivers State, Niger Delta, Nigeria - Momta, Philip Nukebabari; Uzamere, Osewengie; Ezebuiro, Obinna Innocent (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
Most of the trash that businesses and homes make, including heavy metals, ends up in the aquatic environment. Heavy metal pollution is still a big problem in the Niger Delta area of Nigeria when it comes to food safety. The study was done to find out the amount of heavy metals in surface water samples from some creeks in Rivers State, Niger Delta, Nigeria. In Rivers State, Nigeria, samples of surface water were taken from the creeks of Borokiri, Kaa, Okrika, and Eagle Island. Samples were analyzed using standard laboratory methods and an atomic absorption spectrometer (AAS) was used to find out the amounts of heavy metals. Both descriptive and inferential methods were used to analyze the results. In the study, the levels of heavy metals (in mg/l) in surface water were found to be: Cd (0.5186-3.6911), Cu (2.7160-5.9167), Zn (3.1172-6.5031), Cr (1.8972-5.3281), Ba (1.1169-2.8911), Pb (2.2874-4.8069), and Ni (1.9724-5.0691). The levels of heavy metals obtained in this study were above regulatory limits by the World Health Organization (WHO) and the Federal Ministry of the Environment (FMENV). The elevated levels of heavy metals recorded may have come from sewage treatment plants, sewage flows, building sites, illegal oil bunkering and runoff from farms in the study areas. The high amounts of heavy metals in the surface water in the study areas could be harmful to aquatic life and even humans if they eat these contaminated aquatic animals. The results show that there is a significant difference in the amounts of heavy metals in the surface water at the different sites. To stop the Creeks from getting worse from heavy metals, it is suggested that relevant authorities should monitor and control the random dump of household and commercial wastes, as well as untreated wastewater from factories, into the rivers.